2016
DOI: 10.15405/epsbs.2016.08.111
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Moving-Average Trading Strategy: Evidence in Malaysia Equity Market

Abstract: Technical analysis practitioners believe that data on past price and volume provide important and useful information in forecasting future price movements in the financial market. This paper study Optimizing MovingAverage Trading Strategy. We find that the original classical moving average crossover strategies have generated higher risk-adjusted portfolio return as compared to the simple buy-and-hold strategy. The modified MA crossover strategy shows inconsistency in its strategy return as some periods of cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Many academic researchers have studied moving averages relating to market performance (de Souza et al, 2018;Ishfaq Ahmad et al, 2017;Tapa et al, 2016). However, long-term data have been used.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Many academic researchers have studied moving averages relating to market performance (de Souza et al, 2018;Ishfaq Ahmad et al, 2017;Tapa et al, 2016). However, long-term data have been used.…”
Section: Figurementioning
confidence: 99%
“…The moving averages (MA) method is a well well-known method to traders as the indicator is precise and non-debatable, unlike the other 4 Source. TradingView Many academic researchers have studied moving averages relating to market performance (de Souza et al, 2018;Ishfaq Ahmad et al, 2017;Tapa et al, 2016). However, long-term data have been used.…”
Section: Moving Averagesmentioning
confidence: 99%
See 1 more Smart Citation
“…They considered different turning points and calculated the retracement and projection ratios and concluded that Fibonacci retracement proved that the stock prices almost reversed around the Fibonacci ratios and Fibonacci trading could be very useful for traders in the African stock market Otake and Fallou (2013). Tapa et al (2016) examined the profitability of technical analysis using moving average crossover strategy compared with the simple buy and hold strategy on Malaysian equity market Tapa et al (2016). Gurrib (2016) investigated the use of an optimized moving average crossover strategy for the S&P 500 Gurrib (2016).…”
Section: Technical Indicatormentioning
confidence: 99%
“…Noteworthy, fund managers tend to use technical analysis as one of their analytical tools in managing the complex portfolio investments (Ahmad et al, 2017). Previous studies have also shown that certain technical indicators are capable in producing abnormal returns in the stock market (Tapa et al, 2016;Ling et al, 2020). However, the main drawback of the previous findings is that they are database specific and may not generalized to other stocks.…”
Section: Introductionmentioning
confidence: 99%